An Evaluation of Regional Cardiovascular Disease and Cancer Research Needs Using Conference Abstracts - Georgia A. Williamson; Shelly Rodrigo; Elizabeth Blackman; Camille C. Ragin; J. Robert Beck; Marshall K. Tulloch-Reid (Ubiquity Press, 2021)
Background: Despite cardiovascular diseases and cancer being the leading causes of premature mortality in the Caribbean region, there is limited local research available to guide a comprehensive response to this epidemic. Objective: To evaluate cardiovascular disease and cancer research in the Caribbean using abstracts presented at the Caribbean Public Health Agency's (CARPHA) meeting - the longest running annual research conference in the region. Method: Study data (population, intervention/exposure, comparison and outcome) were extracted from abstracts published for the 2006 to 2018 meetings. Additionally, institutional affiliation and geographic location of the first author, countries involved, sample size, study design and use of specialized testing/biomarkers were also extracted. Data were analysed using STATA version 14. Findings: A total of 1,512 abstracts, 728 posters and 784 oral presentations were reviewed. Research on cancer and cardiovascular disease comprised approximately 15% of all abstracts published annually over the review period. Most of the cardiovascular disease studies had cross sectional or survey designs (46%), with very few laboratory-based studies (<2%) and no intervention studies/clinical trials. For cancer research, 30% were cross-sectional studies/audits, 11% were case control studies, 5% were lab based and there were no clinical trials. Almost a quarter of the cardiovascular disease / cancer abstracts over the period originated from Trinidad and Tobago (26%), with Jamaica and Barbados contributing 18% and 15% respectively. Conclusion: These finding highlight the need for additional studies that can provide evidence for interventions and policy to address the region's high cardiovascular disease and cancer burden. A Regional Centre of Research Excellence could support capacity development to facilitate this process.